Global Reform versus Regional Emancipation: the Principles on International Investment for Sustainable Development in Africa - (:unkn) unknown (My University, 2020)
International investment law has been weathering contestation since its inception. It suffices to recall the opposition of capital-importing States to the idea of an international minimum standard expressed in the famous Calvo Doctrine which rejected the standards of compensations for expropriation. Contestation also flared with the rejection of an obligation to provide compensation for the expropriation of foreigners that accompanied the Declaration on the Establishment of the New International Economic Order (NIEO).
Keywords: African Research